Continuous Collision Detection for Ellipsoids - Yi-King Choi; Jung-Woo Chang; Wenping Wang; Myung-Soo Kim; Elber, G. (IEEE transactions on visualization and computer graphics, 2009)
We present an accurate and efficient algorithm for continuous collision detection between two moving ellipsoids. We start with a highly optimized implementation of interference testing between two stationary ellipsoids based on an algebraic condition described in terms of the signs of roots of the characteristic equation of two ellipsoids. Then we derive a time-dependent characteristic equation for two moving ellipsoids, which enables us to develop a real-time algorithm for computing the time intervals in which two moving ellipsoids collide. The effectiveness of our approach is demonstrated with several practical examples.